Corpus stylistics and translation studies: a corpus-assisted study of Joseph Conrad's Heart of darkness and its Italian translations - Mastropierro, Lorenzo (2016)
This thesis carries out a corpus stylistic study of Joseph Conrad’s Heart of Darkness and four of its Italian translations. It investigates the role of textual patterns as building blocks of the fictional world and triggers of literary themes. It also investigates the effects of translation on the relation between textual patterns and the fictional world, and discusses the potential consequences of translational alterations on the text’s themes.